Prognostic and diagnostic value of circRNA expression in prostate cancer: A systematic review and meta-analysis - Xie, Jingling; Jiang, Hui; Zhao, Yuanqing; Jin, Xin rui; Li, Baolin; Zhu, Zixin; Zhang, Limei; Liu, Jinbo (Frontiers in Oncology, 2022)
Background: Circular RNAs (circRNAs) are receiving increasing attention as a novel marker. Our goal was to investigate the diagnostic, clinicopathological, and prognostic utility of circRNAs in Prostate cancer (PCa). Methods: Relevant literature was searched in PubMed, Web of Science, and EMBASE. Sensitivity, specificity, diagnostic odds ratio (DOR), negative likelihood ratio (NLR), positive likelihood ratio (PLR), and the area under the curve (AUC) were calculated to evaluate the diagnostic accuracy of circRNAs expression. CircRNAs’ clinical, pathological, and prognostic value was examined using pooled odds ratios (OR) and hazard ratios (HR). Results: This meta-analysis included 23 studies, with 5 for diagnosis, 16 for clinicopathological parameters and 10 for prognosis. For diagnostic value, the pooled sensitivity, pooled specificity, PLR, NLR, DOR and AUC were 0.82, 0.62, 2.17, 0.29, 7.37 and 0.81, respectively. Up-regulation of carcinogenic circRNAs were associated with poor clinical parameters (Gleason score: OR = 0.222, 95% CI: 0.145-0.340; T classification: OR = 0.274, 95% CI: 0.175-0.430; Lymph node metastasis: OR = 0.353, 95% CI: 0.175-0.716; Tumor size: OR = 0.226, 95% CI: 0.099-0518), and could predict poor survival outcomes. (HR = 2.408, 95% Cl:1.559–3.720, p < 0.001). Conversely, down-regulation of tumor-suppressor circRNAs were also associated with poor clinical parameters (Gleason score: OR = 1.689, 95% CI: 1.144-2.493; T classification: OR = 2.586, 95% CI: 1.779-3.762) and worse prognosis (HR = 1.739, 95% Cl:1.147–2.576, p = 0.006). Conclusion: Our results showed that circRNAs might be useful biomarkers for the diagnosis and prognosis of PCa. Prospero registration number: CRD42021284785.